Histopathological Pattern of Gynecological Malignancies at Tribhuvan University Teaching Hospital, Nepal: A 3 years Study - Khaniya, Bishal (Nepalese Medical Journal, 2021)
Introduction: Gynecological malignancies include malignancies affecting the female reproductive organs ovary, cervix, body of uterus, vulva, vagina, and gestational trophoblastic neoplasia. Materials and Methods: This is a hospital-based retrospective observational study of histopathological confirmed gynecological malignancies conducted in the department of Obstetrics and Gynecology, TUTH, Maharajgunj, Kathmandu for 3 years from April 2016 to March 2018. Results: Among 314 cases enrolled in the study, the most common gynecological malignancy was of ovary (50.63%), followed by the cervix (30.25%), endometrium (9.23%), (4.77%) gestational trophoblastic neoplasia (3.82%), and fallopian tube (1.27%). 71% of the gynecological malignancies presented in early-stage and 29% in late-stage. The most common histopathological diagnosis of ovarian cancer was serous cystadenocarcinoma (30.18%), cervical cancer was squamous cell non-keratinizing type (46.3%), endometrial carcinoma was endometrioid adenocarcinoma (55%), vulval carcinoma was squamous cell carcinoma (86%), fallopian tube carcinoma (100%). The mean age of gynecological malignancy was 49.06 +- 10.08 years. Conclusions: Screening of gynecological malignancy is necessary to identify the disease in early-stage to decrease maternal morbidity and mortality.